Multisensory integration produces an initial response enhancement - Rowland, Benjamin A.; Stein, Barry E. (Frontiers in Integrative Neuroscience, 2007)
The brain has evolved the ability to integrate information across the senses in order to improve the detection and disambiguation of biologically significant events. This multisensory synthesis of information leads to faster (and more accurate) behavioral responses, yet the underlying neural mechanisms by which these responses are speeded are as yet unclear. The aim of these experiments was to evaluate the temporal properties of multisensory enhancement in the physiological responses of neuron in the superior colliculus (SC). Of specific interest was the temporal evolution of their responses to individual modality-specific stimuli as well as to cross-modal combinations of these stimuli. The results demonstrate that cross-modal stimuli typically elicit faster, more robust, and more reliable physiological responses than do their modality-specific component stimuli. Response measures sensitive to the time domain showed that these multisensory responses were enhanced from their very onset, and that the acceleration of the enhancement was greatest within the first 40 ms (or 50% of the response). The latter half of the multisensory response was typically only as robust and informative as predicted by a linear combination of the unisensory component responses. These results may reveal some of the key physiological changes underlying many of the SC-mediated behavioral benefits of multisensory integration.